PERBANDINGAN EFEKTIVITAS PENGGUNAAN ANGIOTENSIN-CONVERTING ENZYME INHIBITOR DAN ANGIOTENSIN RECEPTOR BLOCKER TERHADAP LUARAN KLINIS PASIEN INFARK MIOKARD AKUT (SYSTEMATIC REVIEW) - Chitra Tsania Purna Putri (2022)
Acute Myocardial Infarction (AMI) is a disease with a high level of morbidity and mortality. Renin-Angiotensin System Inhibitor (RASI) drugs such as Angiotensin Receptor Blockers (ARB) and Angiotensin-Converting Enzyme Inhibitors (ACEI) are the standard treatment for AMI patients to prevent adverse clinical outcomes. A systematic literature review comparing the effectiveness of ARBs and ACEIs is needed to determine the optimal choice of therapy in AMI patients. Literature search was conducted on four different databases, namely PubMed, SagePub, ProQuest, and ScienceDirect, published in the last ten years. The literature review was conducted based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols (PRISMA-P) protocol 2020. Results: Nine pieces of literature met the study's inclusion and exclusion criteria. Four pieces of literature state that ACEI is better than ARB. Four other pieces of literature state that there is no significant difference between ACEI use and ARB. One literature states that ARB is better in preventing adverse clinical outcomes in AMI patients. ACEI is considered more effective and is recommended as the primary therapy choice for RASI drugs in AMI patients. However, ARB can still be used as an alternative therapy in AMI patients intolerant of ACEI use.